Development of a computerized 2D rating scale for continuous and simultaneous evaluation of two dimensions of a sensory stimulus - Hoeppli, Marie-Eve; Thurston, Taylor S.; Roy, Mathieu; Light, Alan R.; Amann, Markus; Gracely, Richard H.; Schweinhardt, Petra (Frontiers in Psychology, 2023)
One-dimensional rating scales are widely used in research and in the clinic to assess individuals’ perceptions of sensory stimuli. Although these scales provide essential knowledge of stimulus perception, their limitation to one dimension hinders our understanding of complex stimuli. To allow improved investigation of complex stimuli, a two-dimensional scale based on the one-dimensional Gracely Box Scale was developed and tested it in healthy participants on a visual and an auditory task (rating changes in brightness and size of circles and rating changes in frequency and sound pressure of sounds, which was compared to ratings on one-dimensional scales). Before performing these tasks, participants were familiarized with the intensity descriptors of the two-dimensional scale by completing two tasks. First, participants sorted the descriptors based on their judgment of the intensity of the descriptors. Second, participants evaluated the intensity of the descriptors by pressing a button for the duration they considered matching the intensity of the descriptors or squeezing a hand grip dynamometer as strong as they considered matching the intensity of the descriptors. Results from these tasks confirmed the order of the descriptors as displayed on the original rating scale. Results from the visual and auditory tasks showed that participants were able to rate changes in the physical attributes of visual or auditory stimuli on the two-dimensional scale as accurately as on one-dimensional scales. These results support the use of a two-dimensional scale to simultaneously report multiple dimensions of complex stimuli.